(untitled) (ЕтноАнтропоЗум, 2009)
The investigation of such an important anthropological problem as religion is a complex research challenge. Having in mind the differentiation of specific categories of culture, we find that is necessary to define the different categories of religious systems as well. We are of course focused upon the category of religion that is compatible with folk culture. In ethnological science there is no definitive consensus regarding the utilization of a term that should cover this specific category. Myth, i.e. mythical viewing of the world is the category upon which the whole system of perception and creation of notions related to man and his world are created. Myths refer to the holiest truths about people, their ancestors, their country, so that it is quite understandable that these fundamental elements of the identity of people are valued as holy truths in their awareness and in their mythical knowledge and notions.